Leggendo W. R. Bion - Fagioli, Massimo (Il sogno della farfalla, 2024)
Recent work on rearranging Massimo Fagioli’s personal archive has allowed to rediscover the original typescript of the psychiatrist’s theoretical masterpiece, Death instinct and knowledge. As it is already known, the volume originally included six chapters, one more than what was officially printed for the first time in 1972. Fagioli devoted this “sixth chapter” to a close comparison with the theories of the English psychoanalyst Wilfred R. Bion; specifically with the work Second thoughts, which came out in the Italian translation in 1970. Although some paragraphs of this chapter were already known to the public, reproposing it here in its entirety allows to acknowledge the nature and radicality of the break that Fagioli made from psychoanalytic theories. The comparison with Bion reveals the absolute originality in the development of a general theory of the conscious and unconscious mind, and of the origin of thought.